The migraine eye: distinct rod-driven retinal pathways' response to dim light challenges the visual cortex hyperexcitability theory. Issue 3 (March 2019) - Bernstein, Carolyn A.; Nir, Rony-Reuven; Noseda, Rodrigo; Fulton, Anne B.; Huntington, Shaelah; Lee, Alice J.; Bertisch, Suzanne M.; Hovaguimian, Alexandra; Buettner, Catherine; Borsook, David; Burstein, Rami
Abstract : Abstract: Migraine-type photophobia, most commonly described as exacerbation of headache by light, affects nearly 90% of the patients. It is the most bothersome symptom accompanying an attack. Using subjective psychophysical assessments, we showed that migraine patients are more sensitive to all colors of light during ictal than during interictal phase and that control subjects do not experience pain when exposed to different colors of light. Based on these findings, we suggested that color preference is unique to migraineurs (as it was not found in control subjects) rather than migraine phase (as it was found in both phases). To identify the origin of this photophobia in migraineurs, we compared the electrical waveforms that were generated in the retina and visual cortex of 46 interictal migraineurs to those generated in 42 healthy controls using color-based electroretinography and visual-evoked potential paradigms. Unexpectedly, it was the amplitude of the retinal rod-driven b wave, which was consistently larger (by 14%-19% in the light-adapted and 18%-34% in the dark-adapted flash ERG) in the migraineurs than in the controls, rather than the retinal cone-driven a wave or the visual-evoked potentials that differs most strikingly between the 2 groups. Mechanistically, these findings suggest that the inherent hypersensitivity to light among migraine patients may originate in the retinal rods rather than retinal cones or the visual cortex. Clinically, the findings may explain why migraineurs complain that the light is too bright even when it is dim to the extent that nonmigraineurs feel as if they are in a cave. Abstract : Affected by the disease, the eyes of migraine patients are more sensitive to light than the eyes of nonmigraine subjects.